The use of group processes in high school faculty meetings - Davis, Donald Robert 1930- (s.n.], 1965)
This study consists of two parts: Part 1 deals with the principles of democratic group processes in secondary faculty meetings; Part 2 reports the findings of the study itself, involving a survey of faculty meetings in eight public and private secondary schools in Cebu City having a total enrollment of some 11,992 students.